Pengaruh posisi pengelasan dan gerakan elektroda terhadap kekerasan hasil las baja JIS SSC 41 - I Gusti Ngurah Nitya Santhiarsa; I Nyoman Budiarsa (Department of Mechanical Engineering, University of Udayana, 2008)
At Welding process, position of welding and movement of electrode have influence for the mechanic properties of product. Research into this study influence position of welding and movement of electrode in welding process for the change of hardness properties of Steel material SSC 41.The Method used that is factorial Experiment factorial method, where there are two factor that is position of welding and electrode movement. On welding position there three position that is position flat, vertical and over head. At movement of electrode there three movement that is movement of circle pattern, pattern of Zig-zag,and pattern C. Pursuant to research result, position of welding and movement of electrode used have of level significance influence into hardness value, highest mean Value of hardness Vickers is 513,891 Kg/mm2 there are at welding position variable to the head and C pattern electrode movement, while lower mean value hardness of Vickers is 441,348 Kg/mm2 at welding position variable level off and at zigzag pattern electrode movement.